ANALYSIS OF THE FACTORS AFFECTING TELEMEDICINE USAGE ON ONLINE PURCHASE INTENTIONS FOR HEALTH INSURANCE - Marulitua, Michael Yakub; Hermadi, Irman; Ermawati, Wita Juwita (Ridwan Institute, 2024)
Telemedicine has emerged as a vital tool for providing remote medical consultations, diagnostics, and treatment, especially during the COVID-19 pandemic. However, the integration of telemedicine and health insurance has the potential to enhance healthcare accessibility and affordability. This study aims to analyze the relationships between variables to identify factors influencing the public's intention to purchase online, based on the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB), supported by extension variables such as Risk and User Satisfaction, in line with digital marketing within the field of management. The study employs robust methodological approaches, such as Structural Equation Modeling (SEM) and Partial Least Squares (PLS), offering valuable frameworks for future research while addressing the evolving healthcare landscape in Indonesia. The research findings provide evidence-based insights to address psychological and societal barriers, supports policymakers and healthcare providers in enhancing telemedical strategies, and evaluates the role of government and insurance collaboration in overcoming adoption challenges.